In vitro Cytokine Responses to Virulent PRRS Virus Strains - Ferlazzo, Gianluca; Ruggeri, Jessica; Boniotti, Maria Beatrice; Guarneri, Flavia; Barbieri, Ilaria; Tonni, Matteo; Bertasio, Cristina; Alborali, Giovanni Loris; Amadori, Massimo (Frontiers in Veterinary Science, 2020)
Porcine Reproductive and Respiratory Syndrome (PRRS) affects farmed swine causing heavy direct and indirect losses. The infections sustained by PRRS viruses (PRRSV-1 and PRRSV-2) may give rise to severe clinical cases. This highlights the issue of PRRSV pathogenicity and relevant markers thereof. Since PRRSV strains can be discriminated in terms of immunotypes, we aimed to detect possible correlates of virulence in vitro based on the profile of innate immune responses induced by strains of diverse virulence. To this purpose, ten field PRRSV isolates were investigated in assays of innate immune response to detect possible features associated with virulence. Tumor Necrosis Factor-α, Interleukin (IL)-1beta, IL-8, IL-10, Caspase-1 were measured in cultures of PRRSV-treated Peripheral Blood Mononuclear Cells of PRRS-naïve pigs, unable to support PRRSV replica-tion. Two reference PRRSV strains (highly pathogenic and attenuated, respectively), were included in the screening. The PRRSV strains isolated from field cases were shown to vary widely in terms of inflammatory cytokine responses in vitro, which were substantially lacking with some strains including the reference, highly pathogenic one. In particular, neither the field PRRSV isolates, nor the reference highly pathogenic strain gave rise to an IL-1beta response, which was consistently induced by the attenuated strain, only. This pattern of response was reversed in an inflammatory envi-ronment, in which the attenuated strain reduced the ongoing IL-1beta response. Results indicate that some pathogenic PRRSV strains can prevent a primary inflammatory response of PBMCs, associated with reduced permissiveness of mature macrophages for PRRSV replication in later phases.